Management Aspects Regarding Parameters for Evaluation of The Performance of Educational Systems - Bianca Cezarina ENE; Adrian IOANA; Daniela TUFEANU; Dragos Florin MARCU; Bogdan FLOREA; Daniela Ionela JUGANARU; Daniela Alice LUTA (MANOLESCU) (Communications of International Proceedings, 2020)
This article has as a starting point the definition of the evaluation of an educational system.Thus, severaldefinitions are presented and critically and comparatively analyzed. Based on these analyzes, we have developed a more complete definition that refers both to the four types of resources (material resource, financial resource, material resource and information resource), and to specific management activities. The article also presents and analyzes several parameters for evaluating the performance of educational systems. Among the parameters presented we mention: indicators of performance of the quality of the educational system (resources of the education system; participation; effectiveness and efficiency of education; completed levels and results of education); indicators for quantifying participation in education (participation at all levels of education); indicators for analysis and evaluation of the resources involved.
Keywords: Educational Systems; Management; Evaluation; Performance.